Satellite-tracking the seasonal locations of Trumpeter Swans Cygnus buccinator from Red Rock Lakes National Wildlife Refuge, Montana, USA - Olson, David; Warren, Jeff; Reed, Tom (Wildfowl, 2013)
Six male non-breeding Trumpeter Swans Cygnus buccinator were each fitted with an 80 g satellite transmitter, a U.S. Geological Survey leg band and one red patagial wing tag at Red Rock Lakes National Wildlife Refuge (RRLNWR), Montana, USA, in July 2001 to determine where swans from the refuge spent the breeding, post-breeding, winter and pre-breeding seasons. Of 615 locations recorded, only 34% were of sufficient accuracy (location class 0–3) for analysis. There was no significant difference across seasons in the average distances moved by the marked birds. Individual birds did, however, differ significantly in the average distances that they moved within a season. Managers had hoped that following the termination of the winter feeding programme in winter 1992/93 the birds would disperse from RRLNWR during the winter months. Although the birds in this study did not leave the Greater Yellowstone Area, four of the six birds did winter outside of RRLNWR.